2022
DOI: 10.5194/acp-22-8343-2022
|View full text |Cite
|
Sign up to set email alerts
|

A new assessment of global and regional budgets, fluxes, and lifetimes of atmospheric reactive N and S gases and aerosols

Abstract: Abstract. We used the EMEP MSC-W (European Monitoring and Evaluation Programme Meteorological Synthesizing Centre – West) model version 4.34 coupled with WRF (Weather Research and Forecasting) model version 4.2.2 meteorology to undertake a present-day (2015) global and regional quantification of the concentrations, deposition, budgets, and lifetimes of atmospheric reactive N (Nr) and S (Sr) species. These are quantities that cannot be derived from measurements alone. In areas with high levels of reduced Nr (RD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 104 publications
2
14
0
Order By: Relevance
“…195 In addition, the impacts of NH3 and SOx emissions reductions on NH4 + concentrations over North Africa are significantly greater than from NOx emissions reductions, indicating a dominance of (NH4)2SO4 within SIA in this region. This is consistent with the results reported by Ge et al (2022). They showed that large areas in North Africa are characterised by the SO4 2--rich chemical domain for SIA formation, which means that NH3 is predominantly taken up by SO4 2-, leaving no free NH3 to react with HNO3 to form NH4NO3.…”
Section: Rdn 165supporting
confidence: 92%
See 4 more Smart Citations
“…195 In addition, the impacts of NH3 and SOx emissions reductions on NH4 + concentrations over North Africa are significantly greater than from NOx emissions reductions, indicating a dominance of (NH4)2SO4 within SIA in this region. This is consistent with the results reported by Ge et al (2022). They showed that large areas in North Africa are characterised by the SO4 2--rich chemical domain for SIA formation, which means that NH3 is predominantly taken up by SO4 2-, leaving no free NH3 to react with HNO3 to form NH4NO3.…”
Section: Rdn 165supporting
confidence: 92%
“…All four regions are densely populated and have high Nr and Sr pollution as reported by Ge et al (2022).…”
Section: Definition Of World Regions 150mentioning
confidence: 84%
See 3 more Smart Citations